The human oocyte and cumulus cells relationship: new insights from the cumulus cell transcriptome. - Huang, Z; Wells, D (2010)
It is widely recognized that bi-directional communication exists between the human oocyte and cumulus cells (CCs) which is essential for the production of competent oocytes. CCs originate from granulosa cells (GCs) which differentiate into mural GCs and CCs during follicular antrum formation. CCs are biologically distinct from other follicular cells and perform specialized roles, transmitting signals within the ovary and supporting oocyte growth and maturation during the later stages of follicular development. This review details the results of transcriptomic analysis of CCs and considers what this data can teach us about the biology of CCs and their interactions with the oocyte. We also explore the potential for the gene expression data to reveal novel biomarkers of oocyte quality and assist the optimization of assisted reproductive technologies.